Membangun Etika Kerja Islami: Peran Kepemimpinan Islami dan Lingkungan Kerja Syariah - Anisah, Anisah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of Islamic leadership and a sharia-compliant work environment on Islamic work ethics among Islamic banking employees in Indonesia. Using a quantitative approach with a survey of 150 respondents, the data were analyzed through multiple linear regression. The results indicate that Islamic leadership and a sharia-compliant work environment have a positive and significant influence on Islamic work ethics. These findings strengthen Islamic transformational leadership theory and social cognitive theory, while also providing practical implications for developing a sharia-compliant organizational culture.